SKRINING PENYAKIT KECACINGAN DAN GANGGUAN VISUS PADA SISWA SD DI KELURAHAN SUNGAI PISANG KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Cimi Ilmiawati; Siti Nurhajjah; Nur Afrainin Syah; Mohamad Reza; Efrida Efrida; Eka Nofita; Hasmiwati Hasmiwati; Selfi Renita Rusjdi; Nuzulia Irawati; Sukri Rahman; Elmatris Elmatris; Desmawati Desmawati; Nur Indrawaty Lipoeto; Afriwardi Afriwardi (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
Sungai Pisang Village is a village that has only been accessible by smooth road roads in the past year in Padang City. Previously this village was only accessible by sea and by lousy road. This condition causes the Pisang River community to lag in socio-economic and health aspects. This activity aims to screen for worms in elementary school students in Sungai Pisang village because worms are closely related to environmental health and affect the quality of human resources experiencing growth and development. Screening for worms is carried out by examining fecal preparations. This activity also aims to check visual acuity in elementary students and make references for sharp vision correction to learn well. Visual acuity checks were carried out using a Snellen card. The results of the examination showed that 3/143 students had worms and 3/273 students had visual disturbances. Students with worms are recommended to go to the Puskesmas to be given deworming medicine, and students with visual impairments are facilitated for examination by an ophthalmologist and given glasses if needed.